Sanctions, the World Trade Organisation and the Eurasian Economic Union: examining the legal interrelationships - Mikhaliova, Tatsiana N. (Journal of the Belarusian State University. International Relations, 2022)
The legal framework and practices of World Trade Organisation are examined with relevance to the settlement of disputes over the application of unilateral trade-restrictive measures. Changes are described in the interpretation of the nature of the security exemptions provided in art. XXI of General agreement on tariffs and trade and similar provisions of General agreement on trade in services and Agreement on trade-related aspects on intellectual property rights and invoked by states as justification for trade and economic sanctions. Specifically, there is a tendency to reject – in doctrine and case law – the interpretation of the security clause as self-judging, or not subject to judicial review. It is argued that the necessity test and the principle of good faith should preferably underlie adjudications on the legality of invoking the security exemption. Experiences of the EAEU states with the WTO dispute settlement procedures are considered, and recommendations are made on the merits of the observer status for EAEU at the WTO. Finally, approaches are proposed to consolidate the positions of the EAEU member states on interpreting and applying WTO law in regard to restrictive measures.
Keywords: Dispute settlement body; economic sanctions; Eurasian Economic Union; security clause; World Trade Organisation